2012
DOI: 10.1002/jcb.24375
|View full text |Cite
|
Sign up to set email alerts
|

The influence of RAMP1 overexpression on CGRP‐induced osteogenic differentiation in MG‐63 cells in vitro: An experimental study

Abstract: The aim of this study was to elucidate the influence of receptor activity modifying protein 1 (RAMP1) overexpression on the expression and distribution of calcitonin receptor-like receptor (CRLR) in MG-63 cells. Our research also focused on whether RAMP1 overexpression enhanced the promoting effect of exogenous CGRP on osteogenic differentiation in MG-63 cells. We first constructed a eukaryotic expression vector containing human RAMP1 and stably transfected it into MG-63 cells. Real-time PCR and Western blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…These cells display several osteoblastic traits that are typical of a relatively immature osteoblast and can be induced to mineralize by adding ascorbate-2-phosphate, β-glycerophosphate, and dexamethasone[ 20 ]. In our study, control cells overexpressing EGFP formed mineralizing nodules as detected by von Kossa staining after 21 days induction, consistent with previous reports[ 20 , 21 ]. MG63 cells overexpressing METRNL-EGFP did not exhibit matrix mineralization.…”
Section: Discussionsupporting
confidence: 93%
“…These cells display several osteoblastic traits that are typical of a relatively immature osteoblast and can be induced to mineralize by adding ascorbate-2-phosphate, β-glycerophosphate, and dexamethasone[ 20 ]. In our study, control cells overexpressing EGFP formed mineralizing nodules as detected by von Kossa staining after 21 days induction, consistent with previous reports[ 20 , 21 ]. MG63 cells overexpressing METRNL-EGFP did not exhibit matrix mineralization.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have suggested that αCGRP can directly activate bone-forming osteoblasts because these cells express the calcitonin receptor-like receptor and RAMP1 dimer complex, which serve as the binding site for αCGRP 12) . Moreover, αCGRP was also observed to express on osteoblasts in previous studies 8,13,14) . Other studies have also reported that osteoblast αCGRP receptor activation stimulates adenylyl-cyclase 15) , which induces the activation of protein kinase A (PKA) and phospholipase C 16) , thereby increasing intracellular free calcium 17) with subsequent protein kinase C activation.…”
Section: Discussionsupporting
confidence: 51%
“…Zhang et al, 2017). Moreover, Zhao et al, (2013) confirmed that RAMP1 overexpression promoted exogenous CGRPenhanced osteogenic differentiation in MG-63 cells. These data indicated that RAMP1 may be a potential therapeutic target in regulating CGRP-mediated effects during bone fracture healing (Y.…”
mentioning
confidence: 60%